Layered Double Hydroxides Intercalated with Chlorine Used as Low Temperature Gas Sensors. (2015) - Polese, D.; Mattoccia, A.; Giorgi, F.; Pazzini, L.; Ferrone, A.; Di Giamberardino, L.; Maiolo, L.; Pecora, A.; Convertino, A.; Fortunato, G.; Medaglia, P.G.
Abstract: Layered Double Hydroxides (LDHs) are well known class of materials that since their discovery, happened more than one century ago, have been used in a large range of fields (catalysts, drug delivery media, Oxyanion adsorption, etc.). LDHs are characterized by a large Surface/Volume ratio and a strong ability to adsorb molecules of any kind. Even if these two characteristics make it a very good candidate to be a gas sensor, LDHs have not been deeply investigated yet in this direction. In this work, some evidences of the promising properties of LDHs are shown. In particular, LDHs sensors have been successfully tested in the measuring of three volatile compounds at four different concentrations at room temperature.